Development of Science Digital Comics as a Learning Media of Human Digestive System to Improve Students' Reading Interest - Siregar, Ropinta Sari; Rohani, Rohani (Jurnal Pendidikan MIPA, 2022)
The low score of MAN 1 Medan students in Biology material is due to the low interest in reading. The purpose of this study is to find out how to develop digital comic-based learning media and the influence of the use of digital comics on reading interest in human digestive system material. This type of research uses the ADDIE development model. Which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. Based on the results of material expert validation, the assessment achieved on average is very feasible with a percentage of 100%. Based on the validation results of media experts, the assessment achieved on average is very feasible with a percentage of 94%. And obtained an N-Gain score of 0.56 with a moderate category. It can be concluded that the applied digital comic learning media is effectively used to increase students' interest in reading with a moderate effectiveness category. Keywords: interest in reading, digital comics, ADDIE models, human digestive system DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1435-1445